RETRACTED: Put the control back in the control condition: are brown, pink, and white noise neutral control stimuli? - Færøvik, Ulvhild H.; Vikene, Kjetil; Specht, Karsten (Frontiers in Neuroscience, 2025)
IntroductionWhat are good control stimuli for music perception research? Systematic evaluations of control suitability remain limited. We wanted to examine if control stimuli (brown, pink, white noise, and voice recordings) lead to different emotional ratings in themselves.MethodsAcross two separate studies (n = 84, and 1280, respectively), participants assessed brown, pink, and white noise and voice recordings using a music-emotional perception scale with variations. We used the GEMS-9 scale, and the GEMS-9 scale with the second-order factors ‘sublime’, ‘uneasy’, and ‘vital’.ResultsOur two studies show that brown noise was considered more sublime than white and pink noise, while white noise was considered more uneasy than brown noise, pink noise, and voice recordings in both studies.DiscussionBrown, pink, and white noise is rated emotionally above 3 on unease on a scale from 1 to 7. This means that none of the noise stimuli had minimal emotional ratings and therefore had an emotional effect in themselves. Out of the three noise stimuli, white noise had the highest ratings of unease across both studies. Only voice recordings were considered neutral, defined as having consistently minimal emotional ratings in both studies.